2001
DOI: 10.1021/jp004335e
|View full text |Cite
|
Sign up to set email alerts
|

On the Solubility of Aliphatic Hydrocarbons in 7 M Aqueous Urea

Abstract: Solubility measurements proved that, at 25 °C, methane and ethane are more soluble in water than in 7 M aqueous urea, whereas propane, i-butane, n-butane, and neopentane are more soluble in 7 M aqueous urea than in water. No convincing explanation of these experimental data has been provided up to now. An extension of an emerging theory of hydrophobic hydration is devised to account for the solubility of aliphatic hydrocarbons in 7 M aqueous urea. The conclusions reached are: (a) the work of cavity creation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
81
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 85 publications
15
81
0
Order By: Relevance
“…10,22,27,28 Several urea force fields exist in the literature. [10][11][12][13][14][29][30][31] Computational studies have reproduced the salting out effect ͑decrease in solute solubility͒ of urea solutions on methane and the noble gases, 27,32,33 illustrating that cavity formation is thermodynamically more unfavorable in urea solutions, which is supported by simple models of the salting in and out effects of urea solutions, 34 and in agreement with the observed experimental data on surface tension increases. 35 However, a recent comparison of urea force fields has appeared which demonstrates that current urea models display significantly different degrees of urea aggregation, 15 even though diffraction studies clearly show that urea does not disrupt the hydrogen bonding network of water.…”
Section: Introductionsupporting
confidence: 74%
“…10,22,27,28 Several urea force fields exist in the literature. [10][11][12][13][14][29][30][31] Computational studies have reproduced the salting out effect ͑decrease in solute solubility͒ of urea solutions on methane and the noble gases, 27,32,33 illustrating that cavity formation is thermodynamically more unfavorable in urea solutions, which is supported by simple models of the salting in and out effects of urea solutions, 34 and in agreement with the observed experimental data on surface tension increases. 35 However, a recent comparison of urea force fields has appeared which demonstrates that current urea models display significantly different degrees of urea aggregation, 15 even though diffraction studies clearly show that urea does not disrupt the hydrogen bonding network of water.…”
Section: Introductionsupporting
confidence: 74%
“…Marcus has demonstrated that in aqueous solution, the component ions can be well represented by charged spheres having radii that are close to Pauling‐type crystal ionic radii with a coordination number of 6. We have calculated the values ofkc , ki and kγ for these salts by approximating ethane by a sphere having a radius of 2.19 Å and using the value of giwater=-20.1kJmol-1 as calculated by Jorgensen …”
Section: Resultsmentioning
confidence: 99%
“…Use of the CHARMM force field predicts that urea preferentially interacts with both amide and aliphatic hydrocarbon groups (CH 2 groups in the tri-glycine peptide); this supports the conclusion from several recent simulation studies [21, 22, 55] that interaction between urea and aliphatic groups also plays an important role in urea-induced denaturation. Quantitatively, however, comparison to experimental solubility [57, 58] and X-ray scattering [59] data indicates that the CHARMM force field and perhaps others likely overestimate the interaction between urea and aliphatic groups. Regarding GB, the present study finds that it is excluded mainly from the carboxylate groups and weakly from nonpolar groups, results which are consistent with recent experimental findings [7, 59].…”
Section: Discussionmentioning
confidence: 99%